The Effect of The Cluster Umbrella Strategy on The Achievement of Mathematics Among Second-Grade Intermediate Students (Journal of the College of Basic Education, 2025)
The research sample was randomly selected from the students of the second intermediate grade, and consisted of (50) female students by (25) students in each of the experimental and control research groups, and the two groups were rewarded in the variables of "chronological age, previous achievement in mathematics, previous knowledge in mathematics, intelligence, and the educational level of parents" and the experiment was applied in the second course of the academic year (2024/2025). The research tool has been prepared, which is: the achievement test in mathematics and consists of (25) objective items of the type of multiple choice, and using the equation (Alpha Crowe Nabach) the value of the stability coefficient was (0.72). After completing the application of the experiment, the achievement test in mathematics was applied to the two research groups and after collecting data and using appropriate statistical means, the results showed that the experimental group students who studied mathematics using the cluster umbrella strategy outperformed the control group students who studied the same subject in the usual way. In light of the results of the research, the most important recommendations of the researcher were to train mathematics teachers on how to apply this strategy effectively in the classroom, through workshops and training courses focusing on designing cluster questions and managing classroom discussion, and the most important proposals are conducting a study to find out the impact of the cluster umbrella strategy on higher thinking skills such as: critical thinking, creative thinking, innovative thinking, and problem solving.